2021
DOI: 10.1002/pd.5933
|View full text |Cite
|
Sign up to set email alerts
|

Twin‐twin transfusion syndrome is associated with alterations in the metabolic profile of maternal plasma in early gestation: a pilot study

Abstract: Objective Twin‐twin transfusion syndrome (TTTS) causes perinatal mortality and morbidity in monochorionic twins. The early recognition of and interventional therapy for TTTS is associated with a more favorable overall prognosis. However, the prediction by the use of ultrasound in the first trimester has relatively poor sensitivity and specificity. This study aimed to identify metabolic biomarkers to aid in ultrasound screening of TTTS. Methods Maternal plasma was prospectively collected between 11 and 15 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In the present study, disrupted fatty acid metabolism was observed in untreated TTTS fetuses’ umbilical cord plasma and placental tissue, which is consistent with our previous finding in the later diagnosed TTTS maternal serum collected at early pregnancy ( Yang et al, 2021 ). Compared with the FLC-treated group, the Un group had lower alpha-linolenic acid metabolism in placental metabolomes, and the recipients in the Un group also had less active biosynthesis of unsaturated fatty acids in the cord plasma metabolome.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, disrupted fatty acid metabolism was observed in untreated TTTS fetuses’ umbilical cord plasma and placental tissue, which is consistent with our previous finding in the later diagnosed TTTS maternal serum collected at early pregnancy ( Yang et al, 2021 ). Compared with the FLC-treated group, the Un group had lower alpha-linolenic acid metabolism in placental metabolomes, and the recipients in the Un group also had less active biosynthesis of unsaturated fatty acids in the cord plasma metabolome.…”
Section: Discussionsupporting
confidence: 93%
“…However, since the metabolites in the amniotic fluid could be secreted by the placenta or fetal organs and their secretion could be induced by trophoblast or vessel destruction in FLC surgery or amniodrainage, we still lack solid evidence to confirm the sources of these perturbed metabolites and their role in the pathogenesis of TTTS. Another newly published retrospective cohort study conducted by our team also reported disrupted amino acid and fatty acid metabolism in serum samples prospectively collected during the first gestational trimester of TTTS pregnancies ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation